Establishment of highly sensitive analytical method for chondroitin sulfate by flow injection chemiluminescence. (15th February 2019) - Zhang, Siying; Zhou, Guanglian; Zhang, Xiao; Chen, Dong; Liu, Jian; Liu, Xiumei
Highlights: A simple and sensitive FI-CL method has firstly been established for the determination of CS. The LOD is 5 ng/mL and the analytical time is just 50 s. Compared with the reported methods so far, the established method is simple, accurate, sensitive, rapid and specific for CS determination. The established method is suitable to the analysis of plasma samples. This method provides new ideas and directions for the analysis of other GAGs and lays a foundation for the CS pharmacokinetic study in the future. Abstract: A simple and sensitive flow injection chemiluminescence (FI-CL) method has been developed for the determination of chondroitin sulfate (CS). The method is based on the sensitization effect of enzymatic products of CS on the luminol-H2 O2 system. Experimental parameters affecting FI-CL method such as concentrations of luminol, H2 O2 and NaOH and the standing time of luminol alkaline solution were optimized. Under optimum conditions, the calibration plot between CS concentration and the change of CL intensity was linear in the range of 25 ng/mL∼250 ng/mL. The limit of detection (LOD) was 5 ng/mL and the average relative standard deviation (RSD) of CL intensity was 2.5%. The method was successfully applied to the quantitative analysis of CS concentration in drugs. Compared with the reported methods so far, the established method is simple, sensitive, accurate and rapid.